Copper Modulated Lead‐Free Cs4MnSb2Cl12 Double Perovskite Microcrystals for Photocatalytic Reduction of CO2 - Bo Gao; Changqing Tian; Linfeng Guo; Jinchen Zhou; Zixian Wang; Chengfan Fu; Hongmei Ran; Wei Chen; Qiang Huang; Daofu Wu; Xiaosheng Tang; Zhongtao Luo (Advanced Science, 2024)
Abstract In order to deal with the global energy crisis and environmental problems, reducing carbon dioxide through artificial photosynthesis has become a hot topic. Lead halide perovskite is attracted people's attention because of its excellent photoelectric properties, but the toxicity and long‐term instability prompt people to search for new photocatalysts. Herein, a series of <111> inorganic double perovskites Cs4Mn1‐xCuxSb2Cl12 microcrystals (x = 0, 0.1, 0.2, 0.3, 0.4, and 0.5) are synthesized and characterized. Among them, Cs4Mn0.7Cu0.3Sb2Cl12 microcrystals have the best photocatalytic performance, and the yields of CO and CH4 are 503.86 and 68.35 µmol g−1, respectively, after 3 h irradiation, which are the highest among pure phase perovskites reported so far. In addition, in situ Fourier transform infrared (FT‐IR) spectroscopy and electron spin resonance (ESR) spectroscopy are used to explore the mechanism of the photocatalytic reaction. The results highlight the potential of this class of materials for photocatalytic reduction reactions.